2009
DOI: 10.1007/s00468-009-0321-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature versus species-specific influences on the stable oxygen isotope ratio of tree rings

Abstract: Stable isotopic ratios integrate ecosystem variability while reflecting change in both environmental and biological processes. At sites, where climate does not strongly limit tree growth, co-occurring trees may display large discrepancies in stable oxygen isotopic ratios (d 18 O) due to the interplay between biological processes (competition for light and nutrients, individual tree physiology, etc.) and climate. For a better quantification of the isotope variability within and among trees, the climatic and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…The mean δ 18 O of P. sylvestris cellulose was 1‰ higher than the one of F. sylvatica , which was 0.6‰ higher than the one of Q. petraea . Reynolds‐Henne et al () measured differences about 50% larger (1.5‰ between P. sylvestris and F. sylvatica and 1‰ between the latter and Q. robur ). Szczepanek et al () obtained intermediary results, with a difference between Q. robur and P. sylvestris of 2.1 ‰.…”
Section: Discussionmentioning
confidence: 96%
“…The mean δ 18 O of P. sylvestris cellulose was 1‰ higher than the one of F. sylvatica , which was 0.6‰ higher than the one of Q. petraea . Reynolds‐Henne et al () measured differences about 50% larger (1.5‰ between P. sylvestris and F. sylvatica and 1‰ between the latter and Q. robur ). Szczepanek et al () obtained intermediary results, with a difference between Q. robur and P. sylvestris of 2.1 ‰.…”
Section: Discussionmentioning
confidence: 96%
“…However, a unifying relationship for interpreting observed patterns in d 18 O cell extracted from across tree-rings is lacking. Multiple studies have shown that individual trees may have different d 18 O cell absolute values, even when growing at the same site, under the same conditions (Reynolds-Henne et al, 2009;Richter et al, 2008b;Wang et al, 1998) and authors have concluded that the search for a single environmental signal to explain absolute d 18 O cell values across all sites is futile (McCarroll and Loader, 2004). We have shown elsewhere that the relative change in the carbon isotope (d 13 C) values measured from intra-ring profiles provides valuable quantitative paleoclimate information, despite the fact that absolute values of d 13 C in wood differed between individual trees at the same site (Schubert and Jahren, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…; Reynolds‐Henne et al . ), the underlying mechanisms behind species‐specific affect on δ 18 O cell is currently not well understood. Presumably, such a lack of understanding of δ 18 O cell variability is largely due to the complex involvement of many environmental and physiological factors in influencing δ 18 O cell , thereby impeding precise identification of the source(s) of variation.…”
Section: Introductionmentioning
confidence: 99%
“…Using δ 18 Ocell to reconstruct past climates, or tree physiological responses to climate, requires knowledge of both isotopic variation among individual trees within a given species, and isotopic variation among the species that co-occur at the site (McCarroll & Loader 2004;Leavitt 2010). While co-occurring tree species have been documented to exhibit marked variation in their δ 18 Ocell (Marshall & Monserud 2006;Richter et al 2008;Gebrekirstos et al 2009;Reynolds-Henne et al 2009), the underlying mechanisms behind species-specific affect on δ 18 Ocell is currently not well understood. Presumably, such a lack of understanding of δ 18 Ocell variability is largely due to the complex involvement of many environmental and physiological factors in influencing δ 18 Ocell, thereby impeding precise identification of the source(s) of variation.…”
Section: Introductionmentioning
confidence: 99%